Kehendak Bebas dan Predestinasi dalam Al-Qur’an (Analisis Komparatif Teologi Al-Asy’ari dan Tasawuf Ibn ‘Arabi) - Zifamina, M. Ikhbar Fiamrillah; Abdul Aziz (Indonesian Journal of Islamic Theology and Philosophy, 2025)
Abstract The debate over ikhtiyār (free will) and divine predestination has long occupied a central place in Islamic theological discourse, supported by various Qur’anic verses and prophetic traditions that seem to affirm both positions. This study aims to compare the perspectives of Ash‘arite theology and Ibn ‘Arabi’s Sufi thought regarding the relationship between human will and divine decree. The research employs a comparative analytical method using a library-based approach. The findings reveal that Al-Ash‘ari explains human agency through the concept of kasb (acquisition), which situates human actions within the overarching will of God. Meanwhile, Ibn ‘Arabi approaches the issue through the concept of ḥukm (divine determination), emphasizing that all human actions unfold within the scope of God’s ontological decree. Both scholars critique the notion of absolute free will and lean more strongly toward predestination. These insights contribute to a more balanced understanding of the interplay between human freedom and divine will in Islamic theology. Keywords: Al-Ash'ari; Free Will; Ibn 'Arabi; Predestination